2019
DOI: 10.1108/bjm-11-2018-0373
|View full text |Cite
|
Sign up to set email alerts
|

Alternative regulatory policies, compliance and corporate governance quality

Abstract: Purpose The purpose of this paper is to examine empirically the evolution of corporate compliance with the eighth Company Law Directive (CLD) over time, the relationship between the degree of compliance with the eighth CLD and corporate governance quality (CGQ), and the relative effect of compliance with the eighth CLD and Sarbanes–Oxley Act (SOX) on CGQ. Design/methodology/approach The hypotheses are tested on a sample of EU firms that are cross listed in the EU and the USA and, thus, subject to both EU and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…If so, then there may be significant policy implications from a development perspective because factors that upsurge economic cycle (i.e., inflowFDI, OpeEx, New Technology, regulatory policy, etc.) (Bajra & Čadež, 2020), are likely to have economic returns beyond remittance returns and thus incline their impact on economic growth and reducing inequality. In addition to the impact on the economy and inequality, it also has long-term consequences that mainly affect the export of labor without distinction, then emptying the country of young people in search of a better perspective and possibly increases the possibility of age dependence.…”
Section: Discussionmentioning
confidence: 99%
“…If so, then there may be significant policy implications from a development perspective because factors that upsurge economic cycle (i.e., inflowFDI, OpeEx, New Technology, regulatory policy, etc.) (Bajra & Čadež, 2020), are likely to have economic returns beyond remittance returns and thus incline their impact on economic growth and reducing inequality. In addition to the impact on the economy and inequality, it also has long-term consequences that mainly affect the export of labor without distinction, then emptying the country of young people in search of a better perspective and possibly increases the possibility of age dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Few international cross-country evidences support a positive relationship between a higher proportion of female directors on board for effect on firm financial performance and firm value (Gordini & Rancati, 2017;Terjesen et al, 2016;Vafaei et al, 2015). Bajra and Cade z (2019) reported the relationship between internal audit quality-earnings management and board of directors-earnings management, respectively, in a unique setting of European firms cross-listed in the United States. Results revealed that both internal audit quality and board directors negatively affect the incidence of earnings management, while their interactive impact is positive.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“… These procedures for creating the composite measure of audit committee quality are similar to prior studies (e.g., Bajra & Čadež, 2018b; Bajra & Čadež, 2019). In unreported results, we have replaced this composite measure in Equation by the individual characteristics of the audit committee.…”
mentioning
confidence: 92%